Design and Construction of Mechanical Screw Potato Slicer) - Saud Pangihutan; Ainun Rohanah; Saipul Bahri Daulay (Jurnal Rekayasa Pangan dan Pertanian, 2016)
To serve the need of potato consumers for the ready good potato, it must be processed through post-harvest . Some of the process is cutting and slicing. The need of post-harvest processing that leads to mechanization and to get the optimum gain and high efficiency, potato screw slicer had to be designed and constructed. The study was conducted with literature study, experiment, observation and testing of the equipment. The effective capacity of the equipment was 51,72 kg/h. Basic cost to be incurred in slicing potato with the equipment was Rp. 199,72/kg in the 1st year, Rp. 199,99/kg in the 2nd year,Rp. 200,26/kg  in  the 3rd, Rp. 200,56/kg in the 4th and Rp. 200,87/kg in the 5th. The equipment will reach the break even point if the amount of slicing potato was 889,,30 kg/year. Net present value of the equipment with an interest rate of7,5% was Rp. 391.040.422,54which meant that the business was feasible to run. The internal rate of return was 49,45%. Keywords: equipment design, mechanical screw slicer, potato.